2017
DOI: 10.30684/etj.35.6a.14
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Performance Water Distillation Device by Using Solar Energy

Abstract: Evaluation and an experimental study of the performance of solar water distillation by using collector box with the aperture area of the water distillation of (1*0.6) m. The obtained results are shown that the amount of distilled water increased with increasing the solar radiation temperature. The highest solar water distillation efficiency was found equal to 11.4% for rainy and partially cloudy day between 8am to 10am for 12/4/2016. Also the second higher efficiency was found equal to 5.155 for a sunny day be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The paper [8] used a water distillation device with a collector box with an opening area of (1×0.6) m, with the highest water distillation efficiency analysis results of 11.4 % in sunny weather. The aim of the paper [9] is to analyze and obtain portable water from almost all available sources by utilizing solar energy, the incoming solar radiation is focused on a clean water distillation unit to analyze the distilled sample, and the pH of the distilled product is 8.10±1.06, which is within the WHO limit for drinking water.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The paper [8] used a water distillation device with a collector box with an opening area of (1×0.6) m, with the highest water distillation efficiency analysis results of 11.4 % in sunny weather. The aim of the paper [9] is to analyze and obtain portable water from almost all available sources by utilizing solar energy, the incoming solar radiation is focused on a clean water distillation unit to analyze the distilled sample, and the pH of the distilled product is 8.10±1.06, which is within the WHO limit for drinking water.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Farag et al [99], experimentally studied the performance water Distillation Device by Using Solar Energy". Evaluated the efficiency of the still experimentally at different weather conditions.…”
Section: Solar Still With Wick Materials To Increase Evaporation Ratementioning
confidence: 99%
“…Results showed that distilled water can be obtained even in very bad weather, solar radiation is very low, and the higher amount of distilled water is at higher values than solar radiation. Experimental results also showed high ambient temperature, reducing condensation and distilled water [13]. Analysis of performance of the solar water distilled type hybrid pyramid to purify water and salts, and comparison of performance after adding a center (CPC) discussing performance on condensation the condensation process can be increased either by lowering the temperature of the condensation cap or by increasing the water temperature the use of the center accelerated temperature increase and increase condensation [14].…”
Section: Introductionmentioning
confidence: 97%